The value of digital tomosynthesis of the chest as a problem-solving tool for suspected pulmonary nodules and hilar lesions detected on chest radiography. Issue 5 (May 2015) - Galea, Angela; Dubbins, Paul; Riordan, Richard; Adlan, Tarig; Roobottom, Carl; Gay, David
Graphical abstract: When compared to CXR, DTS has: Superior resolution Better assessment of location in the AP dimension (better at locating a pleural or intrapulmonary lesion) Better characterisation (better at distinguishing between calcified plaque and soft tissue) Removes composite artefact caused by overlying anatomical structures (such as the ribs or pulmonary vessels) DTS has improved sensitivity, specificity and accuracy when compared to CXR. Highlights: DTS is a type of limited angle tomography. Sixty coronal reconstructed images of the chest are produced that combine the superior resolution of radiography with the tomographic benefits of computed tomography. The sensitivity for detecting a suspected lung lesions is 0.65 with CXR and 0.91 for DTS. The high specificity of DTS (1) and the high negative predictive value (0.94) are similar to CT and suggest that if the DTS is normal patients do not need further assessment with CT with significant potential dose savings. 50% of suspected lesions were resolved with CXR, this improved to 96% with DTS. Abstract: Objectives: To assess the capability of digital tomosynthesis (DTS) of the chest compared to a postero-anterior (PA) and lateral chest radiograph (CXR) in the diagnosis of suspected but unconfirmed pulmonary nodules and hilar lesions detected on a CXR. Computed tomography (CT) was used as the reference standard. Materials and method: 78 patients with suspected non-calcified pulmonary nodules or hilar lesions on their CXR were included in the study. Two radiologists, blinded to the history and CT, prospectively analysed the CXR (PA and lateral) and the DTS images using a picture archiving and communication workstation and were asked to designate one of two outcomes: true intrapulmonary lesion or false intrapulmonary lesion. A CT of the chest performed within 4 weeks of the CXR was used as the reference standard. Inter-observer agreement and time to report the modalities were calculated for CXR and DTS. Results: There were 34 true lesions confirmed on CT, 12 were hilar lesions and 22 were peripheral nodules. Of the 44 false lesions, 37 lesions were artefactual or due to composite shadow and 7 lesions were real but extrapulmonary simulating non-calcified intrapulmonary lesions. The PA and lateral CXR correctly classified 39/78 (50%) of the lesions, this improved to 75/78 (96%) with DTS. The sensitivity and specificity was 0.65 and 0.39 for CXR and 0.91 and 1 for DTS. Based on the DTS images, readers correctly classified all the false lesions but missed 3/34 true lesions. Two of the missed lesions were hilar in location and one was a peripheral nodule. All three missed lesions were incorrectly classified on DTS as composite shadow. Conclusions: DTS improves diagnostic confidence when compared to a repeat PA and lateral CXR in the diagnosis of both suspected hilar lesions and pulmonary nodules detected on CXR. DTS is able to exclude most peripheral pulmonary nodules but caution and further studies are needed to assess its ability to exclude hilar lesions.